Effect of Capital Structure, Liquidity, and Earnings Per Share on Profitability in Gold Mining Companies Listed on the Indonesia Stock Exchange - Christina, Mega Aulia; Astuti, Nelly; Hidayati, Nur (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to analyze the effect of capital structure, liquidity, and earnings per share (EPS) on the profitability of gold mining companies listed on the Indonesia Stock Exchange (IDX). The research is important due to the financial volatility faced by the gold mining industry and the limited number of studies focused on this sector in Indonesia. Methodology: A quantitative associative approach was applied using panel data from eight purposively selected gold mining companies during 2020–2024, with 40 observations. Results: Capital structure, liquidity, and EPS simultaneously have a significant effect on profitability. Partially, only capital structure and EPS significantly influence profitability, while liquidity does not. Findings: Efficient capital structure management and consistent EPS growth are key drivers of profitability. Liquidity, however, is not a direct determinant of profit generation in the observed companies. Novelty: This research specifically focuses on gold mining companies in Indonesia, using updated data and a comprehensive panel regression approach. Originality: The study offers new insights into the financial determinants of profitability in the mining sector, emphasizing the role of EPS and capital structure. Conclusion: Effective use of capital and maximizing EPS are essential to improve profitability, while liquidity alone is not a reliable predictor. Type of Paper: Research article